2D‐Layered Carbon/TiO2 Hybrids Derived from Ti3C2MXenes for Photocatalytic Hydrogen Evolution under Visible Light Irradiation. Issue 20 (12th September 2017) - Yuan, Wenyu; Cheng, Laifei; Zhang, Yani; Wu, Heng; Lv, Shilin; Chai, Liying; Guo, Xiaohui; Zheng, Lianxi
Abstract: TiO2 is a promising photocatalytic material for hydrogen generation. However, the fast recombination of electron–holes restricts the photocatalytic performance of TiO2 . Herein, this study demonstrates a 2D‐layered carbon/TiO2 (C/TiO2 ) architecture via CO2 oxidation of 2D‐Ti3 C2, in which the 2D carbon layers provide electron transport channels and improve the hole–electron separation efficiency. Compared to Ti3 C2 support, the thickness of derived carbon supports is significantly reduced, which enhances the light intensity arriving at the surface of TiO2 . The oxidation parameters are investigated systematically. It is found that high temperature and high CO2 gas flux lead to the formation of crystal TiO2 and the oxidation of carbon layers. The bandgap of 2D‐layered C/TiO2 samples is ranged from 2.83 to 2.89 eV. The 2D‐layered C/TiO2 delivers enhanced photocatalytic activity compared with pure TiO2 catalysts. The optimal photocatalytic hydrogen evolution rate of 2D‐layered C/TiO2 is up to 24.04 µmol h −1, which is about 89 times higher than that of pure TiO2 . This research broadens the applications of C/TiO2 hybrids and provides new approach to synthesize novel 2D‐layered materials for photocatalytic applications. Abstract : 2D‐layered carbon/TiO2 (C/TiO2 ) architecture via CO2 oxidation of 2D Ti3 C2 is reported in this work. The 2D carbon layers provide electron transport channels and improve the hole–electron separation efficiency, leading to enhanced phtotocatalytic H2 generation performance by the splitting of water.